A survival kit for the elementary school principal : with reproducible forms, checklists and letters - Bergman, Abby Barry. (Prentice Hall, 1998)
Your role as principal. How to plan for the school year-setting goals and maintaining focus. Shared decision making-the key to a more effective school...